Representasi perempuan berkebaya dalam komunitas seni grafis taring padi : kajian semiotika roland barthes terhadap ambiguitas ideologi gender - Viola Dinda Dwi Hapsari; Novita Wahyuningsih (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study aims to analyze the representation of kebaya-wearing female figures in Taring Padi's graphic art using Roland Barthes' semiotic framework. The primary focus is the ideological gender ambiguity arising from the utilization of traditional kebaya symbols within progressive post-Reformasi 1998 resistance narratives. The methodological approach employs qualitative descriptive analysis with two-stage semiotics (denotation and connotation) and myth formation mechanisms. Primary data is sourced from the publication Taring Padi: Seni Membongkar Tirani (2011), with the main sample being the poster titled